Postfeeding larvae spatial dispersion of Lucilia sericata and Calliphora coloradensis (Diptera: Calliphoridae) - VERGARA-PINEDA, SANTIAGO; DE LEÓN-MÚZQUIZ, HUMBERTO; GARCÍA-MARTÍNEZ, OSWALDO; CANTÚ-SIFUENTES, MARIO; LANDEROS-FLORES, JERÓNIMO; TOMBERLIN, JEFFERY K. (Revista Colombiana de Entomología, 2012)
This is the first study performed in Mexico that analyzes the spatial dispersion of postfeeding larvae using human carrion. The remains of a 70 years old Hispanic male were set in an open area the 8th of November 2008. A total of 77 traps were set at ground level separated 50 cm apart of each other and spread along an area of 4 x 4 m. The larvae were collected in the morning along nine days 12 days after the body was leaved in place. Most of the post-feeding larvae molt into adults. Both larvae and adults were identified to the species level. Lucilia sericata was the more common species with 6,844 specimens out of the 8,439 collected; Calliphora coloradensis was the second with just 718 larvae captured. Other species found were Cochliomyia macellaria, C. minima and Phormia regina. The dispersal pattern was aggregated and not homogeneous.